2010
DOI: 10.4097/kjae.2010.58.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors affecting the pain on injection of propofol

Abstract: BackgroundPain on propofol injection is a well-known adverse effect. We evaluated the clinical factors that affect the pain on injection of propofol to develop a strategy to prevent or reduce pain.MethodsWe conducted a prospective, observational study of 207 adult patients (ASA I-II), and the patients were classified according to gender, age, the body mass index (BMI), the IV site and the side of the IV site. During the 10 seconds after propofol injection, pain intensity was measured on an 11-point numerical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 30 publications
1
34
0
2
Order By: Relevance
“…In another study Hye-Joo Kang et al [22] concluded that the younger age patients, the patients with a peripheral IV site and female patients are more sensitive to pain on the injection of propofol.…”
Section: Discussionmentioning
confidence: 98%
“…In another study Hye-Joo Kang et al [22] concluded that the younger age patients, the patients with a peripheral IV site and female patients are more sensitive to pain on the injection of propofol.…”
Section: Discussionmentioning
confidence: 98%
“…Kang ve ark. (3) yaptıkları çalışmada, genç hastalar, periferik intravenöz yolu olanlar ve kadın hastaların propofol enjeksiyon ağrı-sına daha hassas oldukları gösterilmiştir.…”
Section: Discussionunclassified
“…Çalışmalarda materyal metodta farklılık (enjeksiyon ağrısını değerlen-dirme zamanı, ağrı skalaları), propofol dozu (anestezik-subanestezik), propofolün verilme hızı, intravenöz kanül çapı, enjeksiyonun yapıldığı bölge (el üstü, antekübital bölge), premedikasyon durumu, premedikasyonda kullanılan ajanlar, cinsiyet, hatta kadınlarda menstüreal siklus dönemi ağrıyı etkileyerek farklı sonuçlara neden olabilir. (8,12,(25)(26)(27)(28) Propofolün anestezi indüksiyonu sırasın-daki en belirgin etkisi kardiyak outputu, stroke volümü ve sistemik vaskuler rezistansı etkileyerek kan basıncını düşürme-sidir. (29,30) Propofolle kalp hızı artabilir, azalabilir ya da değişmeden kalabilir.…”
Section: Discussionunclassified